A critical assessment of case reports describing absent uterus in subjects with oestrogen deficiency. (4th April 2019) - Berglund, Agnethe; Burt, Elizabeth; Cameron‐Pimblett, Antoinette; Davies, Melanie C.; Conway, Gerard S.
Summary: Objective: The dual diagnosis of hypoplastic uterus in association with ovarian dysgenesis is regularly reported but the pathogenesis of the association is unclear. The uterus, however, may be invisible to all imaging modalities without at least six months of exogenous oestrogen exposure in complete ovarian failure. We assessed all available case reports in this category to estimate whether the apparent association between primary ovarian insufficiency or Turner syndrome and Mullerian agenesis can be largely accounted for by oestrogen deficiency. Design: A literature review of all cases in which an association between ovarian insufficiency or Turner syndrome and hypoplastic uterus has been reported. Patients: PubMed was searched for all case reports associated with relevant key terms. In total, 22 publications with a total of 25 patients were identified and reviewed; 14 subjects had the normal female karyotype (46, XX), and 11 subjects had Turner Syndrome. Measurements: Proportion of subjects who had been exposed to adequate oestrogen prior to the absent uterine diagnosis. Results: A diagnosis of absent uterus was made prior to exposure to exogenous oestrogen in 22/25 (88%) of subjects with primary hypogonadism including 14/14 females with normal karyotype and 8/11 females with Turner syndrome. Conclusions: Oestrogen deficiency is a possible explanation for most subjects being reported as having Mullerian agenesis in association with Turner syndrome or primary ovarian insufficiency. In the presence of oestrogen deficiency, no conclusion can be made about the status of the uterus until adequate exposure to exogenous oestrogen has been completed and we suggest reassessment of the uterus when full adult dose has been reached towards the end of induction of puberty.